Using Taguchi experimental design to calculate and analyze thermal conductivity for (polyacrylamide – kaolin) composite : DOI: 10.48129/kjs.21061 - Hilal, Raghad Hamid (Kuwait Journal of Science, 2023)
The research is interested in studying the thermal property of the composite material because of its importance in the thermal uses of composite materials. The composite material was prepared with different amounts of kaolin (0, 0.2, 0.5, 0.6, and 0.8 g) in (polyacrylamide -kaolin) composite and its thermal conductivity and specific heat capacity were studied. Taguchi Array L25(5^2), factors 2, Runs 25, columns 25(5^6) Array 12, was used as an experimental design and 25 samples were prepared using this array. The results improved that the thermal conductivity of the composite material decreases with a high kaolin amount toward temperature increase, as well as a case with the composite material's specific heat capacity. Each level in a Taguchi method had the same effect on the thermal conductivity. It's analyzed by calculating the Signal to Noise Ratio (SNRA). Optimum factor levels were identified.